Encyclopedia of Polymer Science and Technology 2018
DOI: 10.1002/0471440264.pst015.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Physical Aging of Polymers

Abstract: This article provides an overview of the most important aspects of physical aging of polymers. First, we briefly introduce basic concepts of the glass transition, that is, the way a nonequilibrium glass is formed. Subsequently, after presenting the way physical aging can be monitored, we describe the main well‐established signatures of physical aging, that is, its nonexponential and nonlinear nature. The next part of the article is dedicated to recent advancements in the physical aging of bulk polymers. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 301 publications
0
3
0
Order By: Relevance
“…Both the stretched-exponential function and the KM relaxation rate are concepts often encountered in the field of physical aging of glasses. 10,[22][23][24][25][26][27][28] Here, the temperature is perturbed while the quantity monitored as the response may be any material property that can be measured fast enough that the sample does not relax appreciably during the acquisition time.…”
Section: Communicationmentioning
confidence: 99%
“…Both the stretched-exponential function and the KM relaxation rate are concepts often encountered in the field of physical aging of glasses. 10,[22][23][24][25][26][27][28] Here, the temperature is perturbed while the quantity monitored as the response may be any material property that can be measured fast enough that the sample does not relax appreciably during the acquisition time.…”
Section: Communicationmentioning
confidence: 99%
“…Many studies were carried out in order to verify the influence of the cooling rate on the crystallization of enantiomerically pure PLA [19,20]. It was found that high crystalline fraction, characterized by large spherulites, was reached with cooling rates lower than 2 °C min −1 .…”
Section: Introductionmentioning
confidence: 99%
“…physical aging | TN formalism | relaxation time activation energy P hysical aging is the term used for changes of material properties over time caused by adjustments of the positions of a system's atoms or molecules (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Although aging and degradation of materials are often due to chemical reactions, physical aging is important for amorphous solids like polymers and oxide glasses during production as well as in subsequent use.…”
mentioning
confidence: 99%